26th COLLEGIUM RAMAZZINI STATEMENT - HEALTH AND SAFETY IN THE WORKPLACE IS A HUMAN RIGHT: THE INTERNATIONAL LABOUR ORGANIZATION (ILO) SHOULD ACT NOW TO IMPLEMENT ITS DECISION, AGREED BY ITS CONFERENCE AND INCLUDED IN ITS CENTENARY DECLARATION, THAT OCCUPATIONAL HEALTH AND SAFETY IS RECOGNIZED AS A FUNDAMENTAL RIGHT AT WORK (FRAW) - Collegium Ramazzini (European Journal of Oncology and Environmental Health, 2023)
In June 2019, at the 108th session of the International Labour Organization’s (ILO) International Labor Con- ference, governments agreed occupational health and safety should be designated a Fundamental Right at Work (FRAW). This decision is included in the ILO Centenary Declaration for the Future of Work. The Collegium Ramazzini notes the ILO conference resolution called on the ILO Governing Body “to consider, as soon as possible” measures for including safe and healthy working conditions in the the ILO’s framework of Fundamental Principles and Rights at Work. The ILO estimates 2.78 million people every year lose their lives to occupational diseases and injuries. The Covid-19 pandemic has increased dramatically this work-related toll. This harm is preventable where occupational health and safety is given the necessary resources and priority. Making occupational health and safety a Fundamental Right at Work will place an obligation on ILO member states to give the issue this priority, with consequent benefits for workers, business and society as a whole. ...